2016
DOI: 10.1016/j.antiviral.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting flavivirus RNA dependent RNA polymerase through a pyridobenzothiazole inhibitor

Abstract: RNA dependent RNA polymerases (RdRp) are essential enzymes for flavivirus replication. Starting from an in silico docking analysis we identified a pyridobenzothiazole compound, HeE1-2Tyr, able to inhibit West Nile and Dengue RdRps activity in vitro, which proved effective against different flaviviruses in cell culture. Crystallographic data show that HeE1-2Tyr binds between the fingers domain and the priming loop of Dengue virus RdRp (Site 1). Conversely, enzyme kinetics, binding studies and mutational analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 33 publications
0
41
0
1
Order By: Relevance
“…4b). Molecular interactions with amino acids of this binding site are important to generate both potent and pan-serotype active NS5 RdRp inhibitors61213. Therefore, these findings indicate some structural determinants that can be explored for the discovery and development of new antiviral against ZIKV NS5 RdRp.…”
Section: Discussionmentioning
confidence: 95%
“…4b). Molecular interactions with amino acids of this binding site are important to generate both potent and pan-serotype active NS5 RdRp inhibitors61213. Therefore, these findings indicate some structural determinants that can be explored for the discovery and development of new antiviral against ZIKV NS5 RdRp.…”
Section: Discussionmentioning
confidence: 95%
“…The discovery of compounds is highly dependent on the development of reliable inhibition assays amenable to high throughput screenings (HTS) using various compound libraries. The selection of lead molecules with NS5 inhibitory activity employed X-ray crystallography (to identify fragments that bind to the protein [81]), or were based on enzymatic inhibition assay or virtual screenings [82,83]. Both the initiation step and the elongation step [84,85] or capping activity were targeted [86].…”
Section: Antiviral Strategies Against Ns5mentioning
confidence: 99%
“…In this context, Tarantino et al reported the biochemical and crystallographic characterisation of a pyridobenzothiazole lead (9) as an inhibitor of flavivirus RdRp in micromolar range possessing very high selectivity against DENV2. [31] Subsequently, optimisation of a pyridobenzothiazole scaffold by a substituted phenyl ring provided a broad-spectrum antiviral agent 10 (Figure 4). [32] Anti-hepatitis C virus Hepatitis C virus (HCV) infection is a major global health concern.…”
Section: Denv Helicase Inhibitorsmentioning
confidence: 99%